The 2009 Analysis of Information Remaining on Disks Offered for Sale on the Second Hand Market - Andy Jones; Craig Valli; Glenn Dardick; Iain Sutherland; G. Dabibi; Gareth Davies (Journal of Digital Forensics, Security and Law, 2010)
The ever increasing use and reliance upon computers in both the public and private sector has led to enormous numbers of computers being disposed of at the end of their useful life within an organisation. As the cost of computers has dropped, their use in the home has also continued to increase. In most organisations, computers have a relatively short life and are replaced on a regular basis with the result that, if not properly cleansed of data, they are released into the public domain containing data that can be relatively up to date. This problem is exacerbated by the increasing popularity and use of smart phones, which also contain significant storage capacity. From the results of the research it remains clear that the majority of organisations and private individuals that are using these computers still remain ignorant or misinformed of the potential volume and type of information that is stored on the hard disks contained within these systems. The evidence of the research is that neither organisations nor individuals have considered, or are aware of, the potential impact of the information that is contained in the disks from these systems becoming available to an unintended third party. This is the fifth study in an ongoing research programme being conducted into the levels and types of information that remain on computer hard disks that have been offered for sale on the second hand market. This ongoing research series has been undertaken to gain an understanding of the level and types of information that remains on these disks, to determine the damage that could potentially be caused if the information was misused, and to determine whether there are any developing trends. The disks used have been purchased in a number of countries.The rationale for this was to determine whether there are any national or regional differences in the way that computer disks are disposed of and to compare the results for any regional or temporal trends. The disks were obtained from a wide range of sources in each of the regions in order to minimise the effect of any action by an individual source.